Correction: Formation of β-(1, 3–1, 6)-d-glucan-complexed [70]fullerene and its photodynamic activity towards macrophages. Issue 45 (9th November 2017) - Ikeda, Atsushi; Akiyama, Motofusa; Sugikawa, Kouta; Koumoto, Kazuya; Kagoshima, Yuta; Li, Jiawei; Suzuki, Toshio; Nagasaki, Takeshi
Abstract : Correction for 'Formation of β-(1, 3–1, 6)-d -glucan-complexed [70]fullerene and its photodynamic activity towards macrophages' by Atsushi Ikeda et al., Org. Biomol. Chem., 2017, 15, 1990–1997.